Trends in Coconut Brown Sugar Production – A Review of Health and Future Prospect in the Industry - Frederick Sarpong; Domoinic Anning; Charlotte Oduro-Yeboah (Turkish Journal of Agriculture: Food Science and Technology)
In recent times, several publications on processing of brown coconut sugar have been carried out, which present an excellent option for health-conscious consumers in the global market. The goal was to discuss and present recent developments in the industry, highlight the numerous health benefits and forecast into the future prospects of the industry. From the discussion, coconut sugar contains all the essential amino acids, various vitamins, minerals, phenolic and antioxidant compounds. These antioxidants are very important in the prevention of heart disease, cancer and inflammatory diseases, whilst the polyphenols inhibited the formation of cancer cells by reducing DNA hypermethylation. Vitamins also play an important role in metabolic reactions by acting as transcription effectors and electron donors. Coconut sugar is also known to prevent kidney stone formation and renal diseases by flushing out formed stones and plays an important role in the revitalization and proper functioning of the kidney due to its high potassium content. With a global trade volume of USD 1.33 billion and a compound annual growth rate (CAGR) of 8%, the industry has great prospects. However, restraints such as high labor intensity, environment-friendly demand, and lack of mechanization require immediate attention to salvage the industry.